Color-changeable urinal pad for pets and preparation method of color-changeable urinal pad

By using core-shell structure microspheres in pet urine pads, the problem of special ink dissolution is solved, and the stable and accurate detection of urine pH changes is achieved, ensuring a timely judgment of the cat's health status.

CN119234717AActive Publication Date: 2025-01-03JIANGSU XIAOCHUAN NEW MATERIAL TECHNOLOGY CO LTD
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
CN202411661015.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-01-03
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

When existing pet urine pads detect cat urine pH, special inks are easily soaked by the water-absorbing layer, affecting the color appearance and resulting in delays in judging health status.

Method used

The core-shell structure microspheres are adopted. The shell layer is a low-melting point polyester, and the core layer is a porous water-absorbing material, adsorbing anthocyanins. The hollow structure increases the solid load fastness and adsorption amount of anthocyanins to prevent dissolution and combine with non-woven Cloth and leak-proof layer to form a color-changing urine pad.

Benefits of technology

Improve the stability and sensitivity of color response, ensure that changes in urine pH value appear in a timely manner, accurately judge the health status of pets, and prevent misjudgment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119234717A_ABST
    Figure CN119234717A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of pet supplies, and particularly relates to a color-changeable urinal pad for pets and a preparation method thereof.The color-changeable urinal pad sequentially comprises a non-woven fabric layer, a quick-absorption layer and a leakage-proof layer from top to bottom; wherein the non-woven fabric layer contains core-shell structure microspheres, a shell layer is made of low-melting-point polyester, a core layer is made of a porous water absorption material, anthocyanin is adsorbed on the core layer, and the non-woven fabric layer and the quick absorption layer are bonded through hot pressing. Color response can be carried out on different pH values of pet urine, then the health condition of a pet is judged, meanwhile, the bonding fastness is improved through low-melting-point polyester, dissolution loss of anthocyanin can be prevented through shell layer hydrophobicity and core layer hydrophilicity structure setting, and therefore the color response stability is improved; moreover, the core-shell structure microspheres are arranged in the non-woven fabric layer, so that color change can be seen from the surface layer in time, and judgment delay caused by blocking of color change is prevented.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of pet products, and in particular relates to a color-changeable urine pad for pets and a preparation method thereof. Background Art

[0002] Cats are carnivores. When they are in a healthy state with a natural diet, they generally produce acidic urine with a pH value of 5.5-7.5, and the optimal range is around 6-6.5. Diet and disease are the main factors affecting the pH value of cat urine. Taking medication, stress, strenuous exercise, etc. can also cause the pH value of cat urine to shift. Most pet cats raised in households mainly eat commercial cat food. The vegetables and grains in it will cause the pH of urine to increase. Eating dry food and drinking too little water will also cause the pH of urine to be alkaline. A small number of cats fed raw food eat more meat, and their urine pH will be acidic.

[0003] In addition, many diseases of cats are also accompanied by the change of urine pH from the normal range to acidic or alkaline. For example, if a cat suffers from metabolic or respiratory acidosis, fever, gout, emphysema, urinary tract stones, kidney stones, diabetes, leukemia and other diseases, the urine pH value will be acidic; if a cat suffers from metabolic or respiratory alkalosis, frequent vomiting, urinary retention, cystitis, urinary tract infection, renal tubular acidosis, chronic glomerulonephritis and other diseases, the urine pH value will be alkaline. When the cat's urine is acidic, calcium oxalate stones are prone to form; when the cat's urine is alkaline, ammonium phosphate crystals are prone to precipitate and form struvite stones; the appearance of stones can easily lead to inflammation of the urinary tract, bladder and kidneys, and in severe cases, the urinary tract is blocked, causing the cat to have hematuria and urine retention, which is life-threatening. Therefore, abnormal cat urine pH can be used as an indication of certain potential diseases to a certain extent, especially cat urinary tract diseases and kidney diseases. Therefore, by testing the pH value of cat urine, potential health problems can be detected early and corresponding measures can be taken in time to keep the cat healthy.

[0004] In order to prevent cats from dirtying the floor with their excrement, they are usually given urine pads. Therefore, the urine pad is designed as a pH indicator color-changing structure, which can timely observe the acid-base status of the cat's urine, and then assist in judging the health status. Patent CN116762712A discloses a pet functional urine pad, including a non-woven fabric layer, a special ink printing area, a polymer water-absorbing layer and a waterproof and anti-leakage layer bonded and arranged in sequence from top to bottom. This scheme uses the principle of pH acid-base color change, and through the setting of a special ink printing area, the urine discharged by the pet's lesions will change color when it encounters the special ink printing area due to the change in the pH value of the body, so as to find out the pet's lesions due to lower urinary tract diseases as soon as possible, and provide reference and guidance for timely treatment. However, the composition of the special ink in this scheme is unknown. Although it is also arranged between the non-woven fabric layer and the water-absorbing layer, due to the lack of other treatment, under the super-absorption of the water-absorbing layer, it is likely to cause the ink to penetrate into the water-absorbing layer with urine, thereby affecting the appearance of color on the surface.

[0005] Therefore, it is necessary to provide an improved pet color-changing urine pad to solve the above problems. Summary of the invention

[0006] The purpose of the present invention is to provide a pet color-changing urine pad and a preparation method thereof. By adsorbing core-shell structure microspheres with anthocyanins, the urine pad can respond to the different pH values ​​of pet urine in color, thereby judging the health status of the pet. At the same time, low-melting-point polyester is used to improve the bonding strength, and its hydrophobicity can also prevent the dissolution loss of anthocyanins, thereby improving the stability of the color response.

[0007] To achieve the above objectives, the first aspect of the present invention provides a core-shell structured microsphere for indicating the pH value of pet urine, wherein the shell layer is a low melting point polyester, the core layer is a porous water-absorbing material, and anthocyanins are adsorbed on the core layer.

[0008] Furthermore, the melting point of the low-melting-point polyester is 80-120° C.; and the porous water-absorbing material is hollow microspheres of acrylamide-acrylic acid copolymer.

[0009] In a second aspect, the present invention further provides a method for preparing the core-shell structured microspheres described above, comprising the following steps:

[0010] S1, dispersing the porogen into deionized water, then adding acrylamide, acrylic acid and potassium persulfate to copolymerize to obtain composite microspheres;

[0011] S2, removing the porogen in the composite microspheres to obtain hollow microspheres of acrylamide-acrylic acid copolymer;

[0012] S3, subjecting part of the ethylene glycol to an esterification reaction with the acrylamide-acrylic acid copolymer hollow microspheres, and then adding terephthalic acid, adipic acid, the remaining ethylene glycol, 2,3-pentanediol and diethylene glycol to an esterification reaction to obtain hollow microspheres coated with low-melting-point polyester;

[0013] S4, immersing and adsorbing the hollow microspheres coated with low-melting-point polyester in an aqueous solution containing anthocyanins, and then taking them out and drying them to obtain core-shell structure microspheres.

[0014] Furthermore, in step S1, the porogen is calcium carbonate with a particle size of 50-500 nm; in step S2, the porogen is removed by dissolving with hydrochloric acid.

[0015] Furthermore, in step S1, the molar ratio of acrylamide to acrylic acid is 1:(2-3); and the copolymerization temperature is 60-80°C.

[0016] Furthermore, in step S3, the catalyst used in the polycondensation reaction is antimony trioxide; the molar ratio of terephthalic acid, adipic acid, ethylene glycol, 2,3-pentanediol and diethylene glycol is 1:0.045-0.055:1.2-1.3:0.45-0.50:0.10-0.12; the molar ratio of ethylene glycol to acrylic acid is (10-30):1.

[0017] In a third aspect, the present invention provides a color-changing urine pad for pets, which comprises, from top to bottom, a non-woven fabric layer, a quick-absorbing layer and a leak-proof layer; wherein the non-woven fabric layer contains the core-shell structure microspheres, or the core-shell structure microspheres obtained by the preparation method, which are used to respond to the different pH values ​​of pet urine in color, thereby judging the health status of the pet.

[0018] Furthermore, the non-woven fabric layer is a polypropylene non-woven fabric containing the core-shell structure microspheres, the leak-proof layer is a PE film; and the quick-absorbing layer is a water-absorbing gel or resin.

[0019] In a fourth aspect, the present invention provides a method for preparing the above-mentioned color-changing urine pad for pets, characterized in that core-shell structured microspheres and polypropylene are compositely spun to obtain a polypropylene composite non-woven fabric; the polypropylene composite non-woven fabric, the quick-absorbing layer and the leak-proof layer are stacked in sequence, fixed by hot pressing, and ultrasonically pressed at the edge of the material to obtain a color-changing urine pad for pets.

[0020] Furthermore, the temperature of the hot pressing fixation is 120-150°C.

[0021] The present invention also provides a diaper for pets, comprising a non-woven fabric layer, a quick-absorbent layer and a leak-proof layer; wherein the non-woven fabric layer contains the core-shell structure microspheres described above, or the core-shell structure microspheres obtained by any of the preparation methods described above, which are used to respond to the different pH values ​​of pet urine in color, thereby judging the health status of the pet.

[0022] Compared with the prior art, the technical solution of the present invention mainly has the following technical advantages:

[0023] The pet color-changing urine pad provided by the present invention adopts a shell layer of low-melting polyester, a core layer of a porous water-absorbing material adsorbed with anthocyanins, and the internal hydrophilicity is greater than the external one, which can improve the internal fixation fastness of anthocyanins, prevent dissolution and exudation under the action of sweat, urine, etc., thereby improving the stability of color response, preventing the judgment from being affected by the change of color over time, and improving the adsorption of urine, so as to timely contact with anthocyanins for color development; the hollow structure can also increase the adsorption amount of anthocyanins, thereby improving the color response sensitivity; the external low-melting polyester is a hydrophobic material, which can improve the compatibility with non-woven fabrics on the one hand, and can be hot-pressed and melted on the other hand to improve the bonding fastness. The present invention can respond to the different pH values ​​of pet urine in color, and then judge the health status of the pet. Moreover, the present invention arranges the core-shell structure microspheres in the non-woven fabric layer, and can timely see the color change from the surface layer, preventing the color change from being blocked and delaying the judgment. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The graphs are the variation of the color difference values ​​of Example 1 and Comparative Examples 1 and 2 with the test time. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0026] The present invention provides a core-shell structure microsphere for indicating the pH value of pet urine, wherein the shell layer is a low melting point polyester, the core layer is a porous water-absorbing material, and anthocyanin is adsorbed on the core layer. The melting point of the low melting point polyester is 80-120°C; the porous water-absorbing material is an acrylamide-acrylic acid copolymer hollow microsphere.

[0027] With such a configuration, the hydrophilicity of the interior is greater than that of the exterior, which can improve the internal fixation fastness of anthocyanins, prevent dissolution and exudation under the action of sweat, urine, etc., and can improve the adsorption of urine, so that it can come into contact with anthocyanins in time to show color; the hollow structure can also increase the adsorption amount of anthocyanins, thereby improving the color response sensitivity; the external low-melting point polyester is a hydrophobic material, which can improve the compatibility with non-woven fabrics on the one hand, and on the other hand, can be hot-pressed and melted to improve the bonding fastness.

[0028] The present invention also provides a method for preparing the core-shell structure microspheres described above, comprising the following steps:

[0029] S1, dispersing the porogen into deionized water, then adding acrylamide, acrylic acid and potassium persulfate to copolymerize to obtain composite microspheres;

[0030] S2, removing the porogen in the composite microspheres to obtain hollow microspheres of acrylamide-acrylic acid copolymer;

[0031] S3, subjecting 1 / 2 to 1 / 5 of the total amount of ethylene glycol to an esterification reaction with the acrylamide-acrylic acid copolymer hollow microspheres, and then adding terephthalic acid, adipic acid, the remaining ethylene glycol, 2,3-pentanediol and diethylene glycol to an esterification reaction to obtain hollow microspheres coated with low-melting-point polyester;

[0032] S4, immersing and adsorbing the hollow microspheres coated with low-melting-point polyester in an aqueous solution containing anthocyanins, and then taking them out and drying them to obtain core-shell structure microspheres.

[0033] The present invention constructs a hollow structure through a porogen, forms a hydrophilic layer through copolymerization of acrylamide and acrylic acid, provides a basis for the adsorption of anthocyanins, and provides carboxyl active groups for the grafting of low-melting-point polyester; ethylene glycol is first esterified to the carboxyl group of acrylic acid to form ethylene glycol acrylate, and then other monomers are added, and the branched monomer helps to form the low-melting-point polyester, which provides a basis for hot pressing bonding.

[0034] In step S1, the porogen is calcium carbonate with a particle size of 50-500 nm, preferably 50-200 nm; in step S2, the porogen is removed by dissolving with hydrochloric acid.

[0035] In step S1, the molar ratio of acrylamide to acrylic acid is 1:(2-3); the copolymerization temperature is 60-80°C. By adjusting the content of acrylamide and acrylic acid, the hydrophilicity and the content of low-melting polyester grafted on the surface can be adjusted. When the acrylic acid content is too low, the coating effect of the low-melting polyester is reduced, causing anthocyanins to dissolve and lose easily, and even penetrate into the quick-absorbing layer with better water absorption, thereby affecting the color development effect. If the acrylic acid content is too high, it will reduce hydrophilicity, affect the loading amount of anthocyanins, and further affect the color sensitivity.

[0036] In step S3, the catalyst used in the polycondensation reaction is antimony trioxide; the molar ratio of terephthalic acid, adipic acid, ethylene glycol, 2,3-pentanediol and diethylene glycol is 1:0.045-0.055:1.2-1.3:0.45-0.50:0.10-0.12; the molar ratio of the total amount of ethylene glycol to acrylic acid is (10-30):1.

[0037] The present invention provides a color-changing urine pad for pets, which comprises a non-woven fabric layer, a quick-absorbing layer and a leak-proof layer from top to bottom; wherein the non-woven fabric layer contains the core-shell structure microspheres, or the core-shell structure microspheres obtained by the preparation method, which are used to respond to the different pH values ​​of pet urine in color, thereby judging the health status of the pet.

[0038] Furthermore, the non-woven fabric layer is a polypropylene non-woven fabric containing the core-shell structure microspheres, and the amount of the core-shell structure microspheres is 5%-15% of the mass of polypropylene; the leakproof layer is a PE film; and the quick-absorbing layer is a water-absorbing gel or resin.

[0039] In a fourth aspect, the present invention provides a method for preparing the above-mentioned pet color-changing urine pad, characterized in that core-shell structure microspheres and polypropylene are compositely spun to obtain a polypropylene composite non-woven fabric; the polypropylene composite non-woven fabric, the quick-absorbing layer and the leak-proof layer are stacked in sequence, hot-pressed and fixed, and ultrasonically pressed at the edge of the material to obtain a pet color-changing urine pad. Furthermore, the temperature of the hot-pressing and fixing is 120-150°C.

[0040] Example 1

[0041] A pet color-changing urine pad comprises, from top to bottom, a non-woven fabric layer - a polypropylene non-woven fabric containing core-shell microspheres, a quick-absorbing layer - a water-absorbing gel and a leakproof layer - a PE film; the preparation method is as follows:

[0042] The core-shell structure microspheres and polypropylene are compositely spun to obtain a polypropylene composite non-woven fabric (the amount of the core-shell structure microspheres is 8% of the mass of the polypropylene); the PE film, the water-absorbing gel and the polypropylene composite non-woven fabric are stacked in sequence, then hot-pressed and fixed at 130°C, and ultrasonically pressed at the edge of the material to obtain a color-changing urine pad for pets.

[0043] The preparation method of core-shell structure microspheres is as follows:

[0044] S1. Calcium carbonate of 150 nm was dispersed in deionized water (mass fraction was 1%), and then acrylamide, acrylic acid (the molar ratio of acrylamide to acrylic acid was 1:2, and the total mass of acrylamide and acrylic acid was 10 times the mass of calcium carbonate) and potassium persulfate were added, copolymerized at 80°C, and then centrifuged and dried to obtain composite microspheres;

[0045] S2, removing calcium carbonate in the composite microspheres with hydrochloric acid to obtain hollow microspheres of acrylamide-acrylic acid copolymer;

[0046] S3, esterifying a quarter of the total amount of ethylene glycol with acrylamide-acrylic acid copolymer hollow microspheres under the action of sulfuric acid, and then adding terephthalic acid, adipic acid, the remaining ethylene glycol, 2,3-pentanediol, diethylene glycol and antimony trioxide for polycondensation to obtain hollow microspheres with low melting point polyester coated on the surface; the molar ratio of terephthalic acid, adipic acid, ethylene glycol, 2,3-pentanediol and diethylene glycol is 1:0.045:1.2:0.45:0.10; the molar ratio of the total amount of ethylene glycol to acrylic acid is 15:1;

[0047] S4. The hollow microspheres coated with low-melting-point polyester are immersed and adsorbed in an aqueous solution containing anthocyanins (red cabbage extract, commercially purchased) (the mass fraction of anthocyanins is 0.5%, and the mass of the hollow microspheres is 10 times the mass of anthocyanins), and then taken out and dried to obtain core-shell structured microspheres.

[0048] Example 2

[0049] The difference from Example 1 is that the molar ratio of acrylamide to acrylic acid is 1:1.

[0050] Example 3

[0051] The difference from Example 1 is that the molar ratio of acrylamide to acrylic acid is 1:3.

[0052] Example 4

[0053] The difference from Example 1 is that the molar ratio of the total amount of ethylene glycol to acrylic acid is 5:1.

[0054] Example 5

[0055] The difference from Example 1 is that the molar ratio of the total amount of ethylene glycol to acrylic acid is 30:1.

[0056] Comparative Example 1

[0057] The difference from Example 1 is that the preparation method of the core-shell structure microspheres is as follows:

[0058] S1. Calcium carbonate of 150 nm was dispersed in deionized water (mass fraction was 1%), and then acrylamide, acrylic acid (the molar ratio of acrylamide to acrylic acid was 1:2, and the total mass of acrylamide and acrylic acid was 10 times the mass of calcium carbonate) and potassium persulfate were added, copolymerized at 80°C, and then centrifuged and dried to obtain composite microspheres;

[0059] S2, removing calcium carbonate in the composite microspheres with hydrochloric acid to obtain hollow microspheres of acrylamide-acrylic acid copolymer;

[0060] S3, immersing and adsorbing the acrylamide-acrylic acid copolymer hollow microspheres in an aqueous solution containing anthocyanidins (red cabbage extract, commercially purchased) (the mass fraction of anthocyanidins is 0.5%, and the mass of the hollow microspheres is 10 times the mass of anthocyanidins), and then taking out and drying to obtain microspheres.

[0061] Comparative Example 2

[0062] The difference from Example 1 is that no calcium carbonate is added during the preparation of the core-shell structured microspheres.

[0063] Take a cat urine sample, add a buffer solution, and prepare different solutions with pH values ​​of 3, 4, 5, 6, 7, 8, 9, 10, 11, and 12 for use. Take the urine pad prepared in Example 1 above, add 1 mL of solutions with different pH values, observe the color development time and color change, and the results are shown in Table 1. Then take 1 mL of the solution with a pH value of 3 and add it to the urine pads prepared in Examples 1-5 and Comparative Examples 1-2, observe the color development time and color change, and the color change after 5 minutes, and the results are shown in Table 2.

[0064] Table 1 Test results of Example 1 in solutions with different pH values

[0065]

[0066] It can be seen from Table 1 that the urine pad prepared by the present invention can produce color changes at different pH values. A colorimetric card is made based on this, which can facilitate users to make timely comparisons, thereby visually observing the pH value of cat urine.

[0067] Table 2 Test results of embodiments and comparative examples

[0068]

[0069]

[0070] As can be seen from Table 2, when the amount of acrylic acid is reduced, it has little effect on the initial color change, but after a certain period of time, the color becomes lighter and unevenly distributed. This may be because the reduction in the content of acrylic acid leads to a decrease in the content of low-melting polyester grafted on the surface, which makes the internal anthocyanins penetrate into the water-absorbing gel layer with better water absorption along with the solution, thus affecting the appearance of the surface color. When the amount of ethylene glycol is reduced, there are similar changes. When the surface is not grafted with low-melting polyester, although the color changes quickly, after 5 minutes of placement, the color becomes significantly lighter, indicating that the anthocyanin dissolution is seriously lost and penetrates into the water-absorbing gel layer with the solution more quickly, resulting in a shorter appearance time of the surface color. If the user does not watch it in time, it is easy to make a wrong judgment. When there is no hollow structure, the color changes slowly due to the reduction in the adsorption of anthocyanins. At the same time, it will also affect the solid fastness of anthocyanins, resulting in lighter color after placement.

[0071] 1 mL of a solution with a pH value of 3 was added to the urine pad prepared in Example 1, and the color obtained after 10 seconds was recorded as the color data of the standard sample. Then, the color data of 30 seconds, 1 minute, 2 minutes, 3 minutes, 4 minutes, and 5 minutes were tested by a colorimeter to obtain the color difference value ΔE compared with the standard sample. The color difference values ​​ΔE of Comparative Examples 1 and 2 at 10 seconds, 30 seconds, 1 minute, 2 minutes, 3 minutes, 4 minutes, and 5 minutes were tested according to the above method. Figure 1 As shown. It can be seen that the color of Example 1 does not change significantly with the increase of the placement time, while although the color of Comparative Example 1 develops quickly, the color changes rapidly with the increase of the placement time, indicating that the color change is unstable and is not conducive to the user to make a correct judgment. Comparative Example 2 develops color slowly, and after placement, the color change is greater than that of Example 1.

[0072] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A core-shell microsphere for indicating pH value of pet urine, characterized in that: The shell layer is low melting point polyester, the core layer is porous water-absorbing material, and anthocyanin is adsorbed on the core layer.

2. The core-shell structure microsphere according to claim 1, characterized in that: The melting point of the low-melting-point polyester is 80-120° C.; the porous water-absorbing material is hollow microspheres of acrylamide-acrylic acid copolymer.

3. A method for preparing core-shell structured microspheres according to claim 1 or 2, characterized in that: The following steps are involved: S1, dispersing the porogen into deionized water, then adding acrylamide, acrylic acid and potassium persulfate to copolymerize to obtain composite microspheres; S2, removing the porogen in the composite microspheres to obtain hollow microspheres of acrylamide-acrylic acid copolymer; S3, subjecting part of the ethylene glycol to an esterification reaction with the acrylamide-acrylic acid copolymer hollow microspheres, and then adding terephthalic acid, adipic acid, the remaining ethylene glycol, 2,3-pentanediol and diethylene glycol to an esterification reaction to obtain hollow microspheres coated with low-melting-point polyester; S4, immersing and adsorbing the hollow microspheres coated with low-melting-point polyester in an aqueous solution containing anthocyanins, and then taking them out and drying them to obtain core-shell structure microspheres.

4. The method for preparing core-shell structured microspheres according to claim 3, characterized in that: In step S1, the porogen is calcium carbonate with a particle size of 50-500 nm; in step S2, the porogen is removed by dissolving with hydrochloric acid.

5. The method for preparing core-shell structured microspheres according to claim 3, characterized in that: In step S1, the molar ratio of acrylamide to acrylic acid is 1:(2-3); and the copolymerization reaction temperature is 60-80°C.

6. The method for preparing core-shell structured microspheres according to claim 3, characterized in that: In step S3, the catalyst used in the polycondensation reaction is antimony trioxide; the molar ratio of terephthalic acid, adipic acid, ethylene glycol, 2,3-pentanediol and diethylene glycol is 1:0.045-0.055:1.2-1.3:0.45-0.50:0.10-0.12; the molar ratio of ethylene glycol to acrylic acid is (10-30):

1.

7. A pet urine pad with changeable color, characterized in that: From top to bottom, it includes a non-woven fabric layer, a quick-absorbing layer and a leak-proof layer; wherein the non-woven fabric layer contains the core-shell structure microspheres described in claim 1 or 2, or the core-shell structure microspheres obtained by the preparation method described in any one of claims 3-6, which are used to respond to the different pH values ​​of pet urine in color, thereby judging the health status of the pet.

8. The pet color-changing urine pad according to claim 7, characterized in that: The non-woven fabric layer is a polypropylene non-woven fabric containing the core-shell structure microspheres, the leak-proof layer is a PE film, and the quick-absorbing layer is a water-absorbing gel or resin.

9. A method for preparing the pet color-changing urine pad according to claim 7 or 8, characterized in that: The core-shell structure microspheres and polypropylene are composite-spun to obtain a polypropylene composite non-woven fabric; the polypropylene composite non-woven fabric, the quick-absorbing layer and the leak-proof layer are stacked in sequence, hot-pressed and fixed at 120-150° C., and the edge of the material is ultrasonically pressed to obtain a color-changing urine pad for pets.

10. A pet diaper, characterized in that: It comprises a non-woven fabric layer, a quick-absorbing layer and a leak-proof layer; wherein the non-woven fabric layer contains the core-shell structure microspheres according to claim 1 or 2, or the core-shell structure microspheres obtained by the preparation method according to any one of claims 3-6, which are used to respond to the different pH values ​​of pet urine in color, thereby judging the health status of the pet.

Citation Information

Patent Citations

  • Composite absorbent particles with superabsorbent material

    CA2607753A1

  • Novel urinal pad with pH display function and manufacturing method thereof

    CN103919649A

  • Dehydration-sensitive thermal time indication device

    CN106546352A

  • Preparation of low-melting-point polyester fiber and application of low-melting-point polyester fiber in natural fiber bonding

    CN114262954A

  • Urine fills up

    CN206482713U